2021
DOI: 10.18632/aging.203556
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of colorectal cancer associated biomarkers: an integrated analysis of miRNA expression

Abstract: Colorectal cancer is one of the leading causes of cancer-related deaths worldwide. This complex disease still holds severe problems concerning diagnosis due to the high invasiveness nature of colonoscopy and the low accuracy of the alternative diagnostic methods. Additionally, patient heterogeneity even within the same stage is not properly reflected in the current stratification system. This scenario highlights the need for new biomarkers to improve non-invasive screenings and clinical management of patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 130 publications
(167 reference statements)
0
12
0
Order By: Relevance
“…The aberrant alternations of genes may affect the cancer pathogenesis and therapeutic response, resulting in cancer progression. Oncogenes and cancer suppressor genes exert opposite effects on the pathological process of cancers ( 1 , 2 ). The exploration of cancer-associated genes and signaling pathways could be beneficial to the diagnose and clinical therapy of most cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The aberrant alternations of genes may affect the cancer pathogenesis and therapeutic response, resulting in cancer progression. Oncogenes and cancer suppressor genes exert opposite effects on the pathological process of cancers ( 1 , 2 ). The exploration of cancer-associated genes and signaling pathways could be beneficial to the diagnose and clinical therapy of most cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, diabetes leads to a higher risk of cardiovascular complications and functional and physical impairment driving adverse outcomes (Fadini and Avogaro, 2010;Prattichizzo et al, 2018;Yun et al, 2018;Jarvie et al, 2019;Yu et al, 2019;Gulsin et al, 2020). microRNAs (miRNAs) are small non-coding RNAs that act as post-transcriptional gene regulators (Ambros, 2004;Krol et al, 2010;Santulli, 2015;Ferrante and Conti, 2017;Fridrichova and Zmetakova, 2019;Stavast and Erkeland, 2019;Mone et al, 2021b;Mone et al, Forthcoming 2022c); miRNAs exert their activity in many biological processes and have been proposed as biomarkers and therapeutic strategies (Creemers et al, 2012;Wronska et al, 2015;Barwari et al, 2016;Chen et al, 2018;Wong et al, 2018;Mone et al, 2021b;Fonseca et al, 2021;Mone et al, Forthcoming 2022c). Many miRNAs have been associated to mitochondrial dysfunction, inflammation, and oxidative stress and their concentration may vary in physiological conditions (Zhang et al, 2014;Hathaway et al, 2018;Wei et al, 2018;Rusanova et al, 2019;Song et al, 2019;Gambardella et al, Forthcoming 2022).…”
Section: Introductionmentioning
confidence: 99%
“…miR-182-5p, miR-183-5p, miR-21-5p, the miR-200 family, miR-7-5p, miR-125b-5p, miR-96-5p, miR-139-5p, miR-99a-5p, miR-497-5p and miR-486-5p have been found to be altered in breast cancer (BC) (48). A total of 26 differentially expressed miRNAs were found to interact with frequently deregulated genes known to be involved in colorectal cancer pathways (49). The majority of these miRNAs could predict the prognosis of patients with colorectal cancer in stages II and III (49).…”
Section: Mirnas In the Development Of Cancer And Cancer Cachexiamentioning
confidence: 99%
“…A total of 26 differentially expressed miRNAs were found to interact with frequently deregulated genes known to be involved in colorectal cancer pathways (49). The majority of these miRNAs could predict the prognosis of patients with colorectal cancer in stages II and III (49). It has been demonstrated that miRNAs can be used for the early detection of oral cancer (50).…”
Section: Mirnas In the Development Of Cancer And Cancer Cachexiamentioning
confidence: 99%